The genetic architecture of temperature-induced partial fertility restoration in A1 cytoplasm in sorghum (Sorghum bicolor (L.) Moench) - D. R. Jordan; R. R. Klein; J. Melonek; I. Small; A. Cruickshank; L. Bradburn; S. Malory; Y. Tao; A. Hathorn; C. H. Hunt; L. T. Amenu; E. S. Mace (Theoretical and Applied Genetics, 2025)
Key message High-temperature-induced partial fertility in CMS sorghum is controlled by multiple genes that are distinct from genes involved in fertility restoration, contributing to reduced diversity in elite females. Abstract Cytoplasmic male sterility (CMS) is used for commercial production of hybrid seed in sorghum. CMS-based hybrid breeding systems require female parental lines (CMS lines) to remain male sterile to prevent self-pollination and enable cross-pollination to generate hybrid seed. However, genetic and environmental factors can lead to the loss of male sterility in the pollen-accepting female parent, resulting in the production of contaminating non-hybrid seeds through self-fertilization with large economic consequences. It is known that high temperatures around flowering time induce sterility breakdown, or partial fertility; however, the genetic control of this phenomenon is poorly understood. To investigate the molecular processes controlling sterility breakdown, a large association mapping population of elite CMS parental lines was used to map the genomic regions controlling partial fertility. In this study, we used genome-wide association studies on a panel of 2049 sorghum lines grown in six field trials at Emerald Queensland representing six different environments. The seed planting was set up in such a way that flowering corresponded with the hottest part of the year. In total 43 significant SNPs were identified, indicating that the trait is controlled by multiple genes; however, previously identified major genes for fertility restoration were not the main cause of partial fertility. Diversity and linkage disequilibrium decay patterns in separate elite male and CMS pools also indicated the constraints on genetic diversity within the female parents due to partial fertility, rather than the frequency of the previously identified major fertility restoration genes. The understanding of the control of sterility breakdown provides new avenues for trait introgression in elite female pools.

Participation in collaborative fisheries research improves the perceptions of recreational anglers towards marine protected areas - Erin M. Johnston; Grant T. Waltz; Rosamaria Kosaka; Ellie M. Brauer; Shelby L. Ziegler; Erica T. Jarvis Mason; Hunter S. Glanz; Lauren Zaragoza; Allison N. Kellum; Rachel O. Brooks; Brice X. Semmens; Christopher J. Honeyman; et al. (Frontiers in Marine Science, 2024)
Collaborative fisheries research programs engage stakeholders in data collection efforts, often with the benefit of increasing transparency about the status and management of natural resources. These programs are particularly important in marine systems, where management of recreational and commercial fisheries have historically been contentious. One such program is the California Collaborative Fisheries Research Program (CCFRP), which was designed in 2006 to engage recreational anglers in the scientific process and evaluate the efficacy of California’s network of marine protected areas. CCFRP began on the Central Coast of California and expanded statewide in 2017 to include six partner institutions in three regions: Northern, Central, and Southern California. To date, over 2,000 volunteer anglers have participated in the program, with many anglers volunteering for multiple years. However, the impacts of outreach, education, and collaborative research on those anglers at the statewide scale are currently unknown. Thus, the objective of the current study was to survey the statewide pool of volunteer anglers to assess the degree to which participation in CCFRP has influenced angler perceptions of MPAs, fisheries management, and conservation. We received 259 completed surveys out of a pool of 1,386 active anglers, equating to an 18.7% response rate. Participation in CCFRP resulted in a significant, positive impact on anglers’ attitudes towards MPAs in California across all regions. Anglers who participated in six or more CCFRP fishing trips had a more positive perception of MPAs than those who participated in fewer trips. Volunteer anglers across all regions perceived that they caught larger fishes, a higher abundance of fishes, and a greater diversity of species inside MPAs, consistent with the ecological findings of the program. These results highlight the benefits of involving community members in collaborative scientific research. Collaboration between researchers and the broader community increases transparency and trust between stakeholders, and results in greater understanding of natural resource dynamics, ultimately producing better management outcomes.

Investigating conspecific CsRV1 transmission in Callinectes sapidus - Julie A. Lively; Matthew I. Spitznagel; Eric J. Schott; Hamish J. Small (Journal of Invertebrate Pathology, 2023)

The sensitivity of the early benthic juvenile stage of the European lobster Homarus gammarus (L.) to elevated pCO2 and temperature - Daniel P. Small; Piero Calosi; Dominic Boothroyd; Stephen Widdicombe; John I. Spicer (Marine Biology, 2016)

Addressing key issues in the consanguinity-related risk of autosomal recessive disorders in consanguineous communities: lessons from a qualitative study of British Pakistanis - A. Darr; N. Small; W. I. U. Ahmad; K. Atkin; P. Corry; B. Modell (Journal of Community Genetics, 2016)

Examining the family-centred approach to genetic testing and counselling among UK Pakistanis: a community perspective - A. Darr; N. Small; W. I. U. Ahmad; K. Atkin; P. Corry; J. Benson; R. Morton; B. Modell (Journal of Community Genetics, 2013)

Allozyme variation in relation to morphology and taxonomy inMedicago sect.Spirocarpos subsect.Intertextae (Fabaceae) - Ernest Small; Suzanne I. Warwick; Brenda Brookes (Plant Systematics and Evolution, 1999)